2023
DOI: 10.1038/s41598-023-32715-0
|View full text |Cite
|
Sign up to set email alerts
|

Collagen type I alters the proteomic signature of macrophages in a collagen morphology-dependent manner

Abstract: Idiopathic pulmonary fibrosis is a progressive lung disease that causes scarring and loss of lung function. Macrophages play a key role in fibrosis, but their responses to altered morphological and mechanical properties of the extracellular matrix in fibrosis is relatively unexplored. Our previous work showed functional changes in murine fetal liver-derived alveolar macrophages on fibrous or globular collagen morphologies. In this study, we applied differential proteomics to further investigate molecular mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Finally, the collagenous matrix itself plays an important role in regulating various processes of macrophage biology, including monocyte-to-macrophage differentiation, lipid uptake [ 258 ], metabolism [ 244 ], polarization [ 131 ], migration mode [ 86 ] as well as their ability to secrete proteases [ 138 , 258 ]. It has been shown in vitro that macrophages increase their MMP-9 secretion when cultured on monomeric type I collagen, in comparison to when they were exposed to the polymerized variant [ 138 ].…”
Section: The Interplay Between Collagen Macrophages and Microcalcific...mentioning
confidence: 99%
“…Finally, the collagenous matrix itself plays an important role in regulating various processes of macrophage biology, including monocyte-to-macrophage differentiation, lipid uptake [ 258 ], metabolism [ 244 ], polarization [ 131 ], migration mode [ 86 ] as well as their ability to secrete proteases [ 138 , 258 ]. It has been shown in vitro that macrophages increase their MMP-9 secretion when cultured on monomeric type I collagen, in comparison to when they were exposed to the polymerized variant [ 138 ].…”
Section: The Interplay Between Collagen Macrophages and Microcalcific...mentioning
confidence: 99%
“…Collagens makes up a large part of the ECM, along with fibronectin, elastin, laminin, tenascin, nidogen, and glycosaminoglycans and their proteoglycans. Macrophages sense collagen morphologies and respond with changes in the expression and activity of metabolism-related proteins [ 12 ]. It is well documented that macrophages cultured in vitro on distinct matrix substrates, elicit different responses, for example, rate of growth, morphology, and expression of inflammatory mediators, which are different from those cultured directly on tissue culture plastics [ 12 , 54 ].…”
Section: Impact Of Biophysical Stimuli On Macrophage Phenotype and Fu...mentioning
confidence: 99%
“…Macrophages sense collagen morphologies and respond with changes in the expression and activity of metabolism-related proteins [ 12 ]. It is well documented that macrophages cultured in vitro on distinct matrix substrates, elicit different responses, for example, rate of growth, morphology, and expression of inflammatory mediators, which are different from those cultured directly on tissue culture plastics [ 12 , 54 ]. Luu TU and co-authors demonstrated a more anti-inflammatory phenotype when macrophages were cultured on laminin and vitronectin, ECM components that proportionally increase in tumours where macrophages contribute to pathology [ 55 ].…”
Section: Impact Of Biophysical Stimuli On Macrophage Phenotype and Fu...mentioning
confidence: 99%